Scientific knowledge and digital democracy in Brazil: how to assess public health policy debate with applied Scientometrics - Piumbato Innocentini Hayashi, Maria Cristina; Rothberg, Danilo [UNESP]; Massao Hayashi, Carlos Roberto (Springer, 2010)
We proposed an original research design based on applied Scientometrics and frame analysis to assess how a citation was made to sustain arguments in documents on public health policies subjected to online public consultation from 2003 to 2008 in Brazil. So we built on citation studies to create a new scale to estimate why a scientific work was mentioned in our sample of 278 citations. We found that government branches make citations mainly to value their arguments, not to explain them, and that contributors mainly make citations in such a way that could discourage others from engaging in digital democracy.
Keywords: Applied Scientometrics; Digital democracy; Citation studies